The Correlation Between Competitive State Anxiety and The Frequency of Unforced Errors in The Serving Technique of Badminton Athletes - damayanti, enarnimas; Hazar, Fatih; Khanina, Naila; Ashari, Sani (Journal of Racket Sports Performance & Science (JRSPS), 2025)
Background: In badminton, the serve is the only technique that is entirely under the athlete’s control, yet ironically it is often the source of unforced errors (UE) in competitive situations. Research Objectives: This study aims to analyze the correlation between competitive state anxiety and the frequency of unforced errors in the serving technique of badminton athletes. Specifically, this study examines the relationship between three dimensions of anxiety (cognitive, somatic, and self-confidence) and the number of serving UE. Methods: This study used a quantitative, correlational design. The sample (n=20) comprised badminton athletes (aged 17-22 years) selected via purposive sampling from an intensive training club. Anxiety data were collected using the Competitive State Anxiety Inventory-2 (CSAI-2). Unforced error (UE) data were collected via direct observation during simulated matches. Analysis used the Pearson Product-Moment correlation. Results: The results of the study show (1) A positive and significant correlation between cognitive anxiety and UE service (r = 0.680, p < 0.01); (2) A positive and significant correlation between somatic anxiety and service UE (r = 0.552, p < 0.05); and (3) A negative and significant correlation between self-confidence and service UE (r = -0.721, p < 0.01). These findings indicate that the mental and physical components of anxiety have a strong relationship with service performance. Conclusion: The main conclusion is that a significant relationship exists between competitive anxiety and unforced service errors. As hypothesized, increased anxiety (cognitive and somatic) was closely related to more service errors, while high self-confidence was related to fewer errors.